Chicken Soup For The Preteen Soul : 101 Stories Of Changes, Choices And Growing Up for Kids Ages 9-13 - Jack Canfield, Mark Victor Hansen, Patty Hansen, Irene Dunlap & Rusty Fischer
Filled with stories from and about readers between the ages of ten and thirteen, this inspiring guide to a difficult period covers personal identity, violence, family issues, and the opposite sex, among other topics. Simultaneous. 500,000 first printing.